A glance at molecular mechanisms underlying cisplatin-induced nephrotoxicity and possible renoprotective strategies: a narrative review (Faculty of Medicine Universitas Indonesia, 2019)
Cisplatin is a platinum-based drug that is usually used for the treatment of many carcinomas. However, it comes with several devastating side effects, including nephrotoxicity. Cisplatin toxicity is a very complex process, which is exacerbated by the accumulation of cisplatin in renal tubular cells via passive diffusion and transporter-mediated processes. Once cisplatin enters these cells, it induces the formation of reactive oxygen species that cause cellular damage, including DNA damage, inflammation, and eventually cell death. On a small scale, these damages can be mitigated by cellular antioxidant defense mechanism. However, on a large scale, such as in chemotherapy, this defense mechanism may fail, resulting in nephrotoxicity. The current article reviews the molecular mechanisms underlying cisplatin-induced nephrotoxicity and possible renoprotective strategies to determine novel therapeutic interventions for alleviating this toxicity.